2021
DOI: 10.1088/1741-2552/abf399
|View full text |Cite
|
Sign up to set email alerts
|

Effect of force accuracy on hemodynamic response: an fNIRS study using fine visuomotor task

Abstract: Objective. Despite converging neuroimaging studies investigating how neural activity is modulated by various motor related factors, such as movement velocity and force magnitude, little has been devoted to identifying the effect of force accuracy. This study thus aimed to investigate the effect of task difficulty on cortical neural responses when participants performed a visuomotor task with varying demands on force accuracy. Approach. Fourteen healthy adults performed a set of force generation operations with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 68 publications
1
13
0
Order By: Relevance
“…During the visuomotor task, we observed typical hemodynamic activation on the contralateral and ipsilateral sensorimotor regions, which is consistent with studies reporting bilateral activation patterns induced by complex unimanual motor tasks, such as sequential finger movements [66] and the use of chopsticks [67]. Compared with simple movements or force control tasks, the visuomotor task required frequent transformations of the online visual feedback into force adjustment and mainly involved visual information processing, force error correction and their complex temporal interactions, leading to abundant recruitment of the bilateral sensorimotor areas [46]. Furthermore, our results demonstrated that the adaptive task difficulty can induce increased activation (i.e.…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…During the visuomotor task, we observed typical hemodynamic activation on the contralateral and ipsilateral sensorimotor regions, which is consistent with studies reporting bilateral activation patterns induced by complex unimanual motor tasks, such as sequential finger movements [66] and the use of chopsticks [67]. Compared with simple movements or force control tasks, the visuomotor task required frequent transformations of the online visual feedback into force adjustment and mainly involved visual information processing, force error correction and their complex temporal interactions, leading to abundant recruitment of the bilateral sensorimotor areas [46]. Furthermore, our results demonstrated that the adaptive task difficulty can induce increased activation (i.e.…”
Section: Discussionsupporting
confidence: 87%
“…The visuomotor task required participants to move a pen-shaped tool along a planar ring path and to produce a constant force against the plane under visual guidance, the same as a previous work did [46]. During the task, the participants held the end effector of a haptic device (Touch, 3D Systems Inc., USA) with their right hands and drew a circle within the range of a circular ring.…”
Section: Visuomotor Taskmentioning
confidence: 99%
See 3 more Smart Citations